(untitled) (Research, Society and Development, 2022)
Studies related to the use of homeopathy in dentistry are scarce in the scientific environment, and also at the undergraduate level. The objective of the present study was to analyze the knowledge of dentists about homeopathy in the city of Redenção-PA, through an online questionnaire applied to professionals, in order to analyze how knowledge about homeopathy is inserted among the dental professionals in a municipality, with a qualitative, explanatory and deductive character, delimited by existing records in the literature of authors in the field of dental homeopathy. This analysis made it possible to establish a bridge that correlates the scarcity of studies in the area with the little knowledge of professionals on the subject and the prevalence of conventional therapy today. To serve as a stimulant to professionals in this region a humanistic and holistic therapy. From the results found, we only obtained negative responses regarding the existence of professionals in the area of ​​this region, on the other hand, we observed a large number of young professionals interested in having qualifications in homeopathy.